Boundary Criteria for the Stability of Delay Differential-Algebraic Equations. (1st July 2015) - Sun, Leping; Cong, Yuhao
Abstract : This paper is concerned with the asymptotic stability of delay differential-algebraic equations. Two stability criteria described by evaluating a corresponding harmonic analytical function on the boundary of a certain region are presented. Stability regions are also presented so as to show the method geometrically. Our results are not reported.